2018
DOI: 10.1016/j.saa.2017.07.042
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of carbohydrates and lignin molecular structure spectral profiles to nutrient profile in newly developed oats cultivars and barley grain

Abstract: The objectives of this study were to quantify the chemical profile and the magnitude of differences in the oat and barley grain varieties developed by Crop Development Centre (CDC) in terms of Cornell Net Carbohydrate Protein System (CNCPS) carbohydrate sub-fractions: CA4 (sugars), CB1 (starch), CB2 (soluble fibre), CB3 (available neutral detergent fibre - NDF), and CC (unavailable carbohydrate); to estimate the energy values; to detect the lignin and carbohydrate (CHO) molecular structure profiles in CDC Nass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 30 publications
1
13
0
Order By: Relevance
“…Characteristically, corn grains have a stronger protein matrix around starch granules than other cereals, which hinders the action of digestive enzymes and amylolytic bacteria, which interferes with ruminal degradability (6) . And ground oat have a higher proportion of hull compared to ground barley, so the DMD at 24 h and the NDFR were lower, corroborating literature data (12) , which also point to a lower digestible fraction for grain oat varieties compared to grain barley.…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…Characteristically, corn grains have a stronger protein matrix around starch granules than other cereals, which hinders the action of digestive enzymes and amylolytic bacteria, which interferes with ruminal degradability (6) . And ground oat have a higher proportion of hull compared to ground barley, so the DMD at 24 h and the NDFR were lower, corroborating literature data (12) , which also point to a lower digestible fraction for grain oat varieties compared to grain barley.…”
Section: Resultssupporting
confidence: 87%
“…As for the NDF content, among these feedstuffs, the ground oat had the highest NDF content. Prates et al (12) evaluated two oat varieties, and found higher values of NDF and acid detergent fiber (ADF) in relation to barley grain. These differences in fiber content are due to the proportion of hull and grain between the cereals, with oats having a higher proportion of hulls.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This discrepancy could be attributed to ingredient types and spectral processing methods. Spectra were not normalized in the previous publication, which could result in the inclusion of variations from sample thickness during spectra collection . Another study conducted with barley and corn silage discovered a negative correlation between TCA and effective NDF degradation, which was not seen in our study, although TC4 height was negatively correlated with NDF degradation.…”
Section: Resultsmentioning
confidence: 95%
“…Spectra were not normalized in the previous publication, which could result in the inclusion of variations from sample thickness during spectra collection. 22,26 Another study conducted with barley and corn Structural parameters: TC1-TC4, four major peaks in TC region at ca. 1026 (TC1) 1074 (TC2), 1104 (TC3) and 1149 (TC4) cm −1 , respectively; TCA, TC peak area (ca.…”
Section: Correlations Between Spectra Parameters and Nutrition Profilmentioning
confidence: 99%